Statistical Concepts Utilized to Derive a QSAR and Their Application to Pharmaceutical Research - VANDERKAR, GAURAV; JAIN, DEEPTI; JAIN, SURENDRA (Asian Journal of Chemistry, 2010)
The combinatorial possibilities of hypothetical strategy for even simple systems can be explosive. For example, the number of compounds required to be synthesized in order to place 10 substituents on the four open positions of an asymmetrically disubstituted benzene ring system is ca. 10000. The alternative to this approach of compound optimization is to develop a theory that quantitatively relates variatioins in biological activity to changes in molecular descriptors that can easily be obtained for each compound. The present article explains the statistical concepts used to derive a QSAR and reviews the application of these techniques to pharmaceutical research.